Risk of infection in elderly patients with AML and MDS treated with hypomethylating agents - Pagano, Livio; Busca, Alessandro; Candoni, Anna; Criscuolo, Marianna; Della Porta, Matteo Giovanni; Fianchi, Luana; Lessi, Federica; Marchesi, Francesco; Voso, Maria Teresa (Acta Biomedica Atenei Parmensis, 2018)
The aim of this small volume is to raise awareness among Italian hematologists using hypomethylating drugs about risk - and even more important about “risk management” - and the treatment of the infectious events that may arise during therapy with these drugs. Since we wanted this review to be an extremely practical tool, we have included the most recent clinical case studies, the indications provided by the guidelines and expert opinions. Infectious complications are among the most common adverse events that can arise during treatment with hypomethylating drugs. For this reason, a large portion of the chapters of this small volume has been dedicated to a detailed description (on the basis of an attentive review of the literature) of what the hematologist can expect to encounter in terms of risk of infection, in patients treated with azacitidine or decitabine, and to the preventive investigations to carry out and the active prophylaxis measures recommended before commencing treatment with these drugs. What led us to write this book was the conviction that the critical sharing of the studies published in literature and of our personal experiences could contribute to prompting reflection on how we operate and that this, in turn, would lead to the best possible management of these treatments, both in patients with myelodysplasia and in patients with acute myeloid leukemia, preventing - and efficiently managing - infectious events - during therapy. We should not be misled by the fact that the treatments are prevalently administered on an outpatient basis; these patients due to their disease and, in particular, to their age, are extremely frail, and infectious and hemorrhagic complications are the main causes of their admissions to hospital. But expert knowledge and management of the risks of infection can guarantee better management of their needs on an outpatient basis, with undeniable advantages for the clinic but, first and foremost, for the patients.